Strategic marketing of telecom leaders in the world - Müller, Michal (2010)
This diploma thesis deals with the topic of the strategic marketing which is applied on the telecommunication market. A special focus is devoted to the new marketing environment (specifically to the new and modern marketing concepts, tools and channels). The reader can learn about world telecommunication leaders and their usage of the strategic marketing. A very interesting comparative analysis of those leaders is presented. All the results and assumptions are verified by own market research which studied the telecommunication value for the customer and the attitude of customers to the strategic marketing. A visionary future development of the strategic marketing is forecasted at the end.